Determinant’s of Audit Quality - D Deliana; Abdul Rahman; Rizki Syahputra; L Listiorini; Karyn SImbolon (Universitas Pendidikan Indonesia, 2023)
The objective of this study is to provide empirical evidence of how auditor accountability, competence, and integrity impact the quality of audits. The research used quantitative methods through questionnaires distributed directly to respondents and collected from 30 sample. The structural measurement and evaluation model using Smart PLS 4 software. The test results indicate that the accountability variable does not impact the quality of the audit. The quality of audits is improved when auditors possess both competence and integrity. Auditors require knowledge and experience when making decisions. The effectiveness of an audit greatly depends on the auditor's competence and integrity. Auditors must have great curiosity, be broad-minded, and be able to carry out analytical reviews in carrying out audit tasks, and auditors must be able to manage time well to complete each audit work, audit results reports can be accounted for by the auditor and not avoid or blame other people who may result in harm to others. Auditors as the spearhead of the implementation of audit tasks must always improve the knowledge so that the application of knowledge can be maximized in practice. The novelty of this research from previous research is that the previous variables used Independence, Complexity of Tasks, and Auditor Competency on the Audit Quality variables, while this research uses Accountability and Integrity variables as independent variables, the research location was carried out in a different place, namely the previous research was carried out at KAP Bali while this research was conducted at KAP Medan City.